THE INFRASTRUCTURAL POWER OF PROGRAMMATIC ADVERTISING NETWORKS: ANALYZING DISINFORMATION INDUSTRIES IN BRAZIL - Dos Santos JR, Marcelo Alves; D’Andrea, Carlos (AoIR Selected Papers of Internet Research, 2023)
The informational disorder that sprawls through multiple state-nations, exacerbated by violent uprisings and coup attempts such as the US Capitol Storm on January 6th, 2021 and the Brazilian coup attempt on January 8th, 2023, has shed new light on the political economy of disinformation industries. In particular, it brings to the forefront the problem of economic incentives for creating and spreading disinformation. This paper builds on critical platform and infrastructure research literature for analyzing the multilateral infrastructural power of programmatic advertising networks. Our research questions are: how is power exercised by programmatic advertising infrastructures while managing its multilateral relationships? In terms of technicities, governance and business models, how does these infrastructures enable or reinforce desinformation disorder? This case study draws on a multi-methodological approach, combining digital methods research and critical analysis of platform documents. The empirical data obtained has 95.269 ads collected on the website (data scraped with a Python script developed by one of the authors) during the election month. Empirical data show that MGID, a native advertising platform, placed 54% of the advertisements on Terra Brasil Notícias. Google Ads was the second largest provider of digital ads on TBN, despite its policy`s restrictions on sellers that host unreliable or harmful content on issues such as health, climate, elections and democracy. Findings from the Brazilian case also contribute to understanding the infrastructural power of big tech governing the monetization of publishers in the Global South.